Restorasi Perpustakaan Sebagai Upaya Mengaktifkan Kembali Perpustakaan Sekolah di SMP PGRI 1 Serang - Sukirno Sukirno (Konsienti : Community Services Journal, 2023)
The purpose of this community service activity is to help schools reactivate libraries that have not been functioning for 2 years due to a collapsed library room. The method used in this activity is the Library Restoration method which includes moving the library space, cleaning and rearranging room layouts, re-sorting library book collections, codifying book identities, displaying book collections and creating a library book collection database. The result of this dedication is that the school library is functioning again and the collection of library books has a database so that it can help improve the quality of the learning process for teachers and students by making the library a center for literacy and numeracy